DESIGN AND EVALUATION OF CARABINER USING FINITE ELEMENT ANALYSIS - Divlan Audie Sentanu; Muhammad Akhsin Muflikhun (Jurnal Rekayasa Mesin, 2022)
A carabiner is a fall protection safety tool that is used in various outdoor and indoor activities, most known usage is at climbing and high-risk work related to elevation. A standard carabiner is capable to withstand at least 7 kN of static load. In this study, we only observe how carabiners respond in certain static loads by using simulation software and comparing the result with the standard of carabiners. We use F1956-13 as a standard of the test procedure, and aluminum alloy 6061 as the material. After the study from simulation result, it shows that stress and deformation change linearly with loads. But the safety factor has different behavior, after the load applied increases over 1 kN the slope decreases significantly, and the safety factor is around 0,17 at 7 kN applied load. Besides that, we understand that design analysis by simulation is a good method to obtain the optimal geometry, or shape of the model, but computational simulation cannot replace physical mechanical tests.